"Sometime We Stir Up a Hornet's Nest" Practitioners and Paradigms of Genetic Counselling - Mitchell, Lisa, M. (My University, 1987)
The central investigative concern of this thesis is the culture of genetic counselling in Canada--a specialized health service providing information and assistance to families at risk from genetic disorders. In particular, this study describes the variability that exists in the way in which genetic counsellors view their profession and explores the factors that contribute to this variability. The genetic counsellors' training, division of roles, view of their responsibility toward clients, and the historical and contemporary context in which they practise contribute to understanding the "individuals' versions of the culture of [genetic counselling]'' (Hahn 1985:53). Three means of inquiry are utilized: extensive library research, responses from a Canada-wide questionnaire sent to genetic counsellors, and ethnographic interviews. The history of genetic counselling has been described as a series of changes from research to medicine to psychosocial concerns. Current definitions of adequate genetic care, however, stress attention to both the medical genetic and psychosocial aspects of genetic disorders suggesting that both a medical and a psychosocial paradigm now exist in genetic counselling. I argue that the association between these two paradigms is unclear, thus producing tension and ambiguity for practitioners. Genetic counsellors divide themselves into three groups--MD/MD-PhDs who are the central caregivers, PhD geneticists who are primarily involved in research, and nonMDs/nonPhDs such as nurses, social workers and master's level genetic associates who are often doing clinic-oriented clerical jobs. Nevertheless, indicative of the uneasy relationship between the paradigms of genetic counselling, considerable debate exists in the field about who should be providing genetic counselling. A further example of this paradigmatic tension concerns the implementation of genetic counselling goals, especially for physician geneticists, the central caregivers. In particular, genetic counsellors face the problematic task of "doing something" for their clients, making them aware of their options, without influencing the client's decision making. The contemporary context of genetic counselling is predominantly a medical one; although psychosocial concerns are acknowledged as important for adequate genetic care, the means for dealing with them are not clear. I suggest that the response to the underlying tensions in genetic counselling is ultimately an individually-constructed response, based on the individual practitioner's experience, interpretation of the facts, and notion of the boundaries of their responsibility in medicine.
Practitioners and Paradigms of Genetic Counselling
Keywords: genetics, genetic counselling, paradigms of genetic counselling, practitioners of genetic counselling